A way of seeing people and place: Phenomenology in environment-behavior research - Seamon, David (Plenum, 2009)
This review examines the phenomenological approach as it might be used to explore environmental and architectural issues. After discussing the nature of phenomenology in broad terms, the review presents two major assumptions of the phenomenological approach: (1) that people and environment compose an indivisible whole; (2) that phenomenological method can be described in terms of a “radical empiricism.” The review then considers three specific phenomenological methods: (1) first-person phenomenological research; (2) existential-phenomenological research; and (3) hermeneutical-phenomenological research. Next, the article discusses trustworthiness and reliability as they can be understood phenomenologically. Finally, the review considers the value of phenomenology for environmental design.
Keywords: Phenomenology; Place; Architecture; Landscape; Environmental experience; Home